2010
DOI: 10.1051/0004-6361/201014210
|View full text |Cite
|
Sign up to set email alerts
|

Radiative transfer with scattering for domain-decomposed 3D MHD simulations of cool stellar atmospheres

Abstract: Aims. We present the implementation of a radiative transfer solver with coherent scattering in the new BIFROST code for radiative magneto-hydrodynamical (MHD) simulations of stellar surface convection. The code is fully parallelized using MPI domain decomposition, which allows for large grid sizes and improved resolution of hydrodynamical structures. We apply the code to simulate the surface granulation in a solar-type star, ignoring magnetic fields, and investigate the importance of coherent scattering for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
174
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 69 publications
4
174
0
Order By: Relevance
“…We therefore assume a static medium and LTE for the gas opacity, which thus depends only on the local gas temperature and the gas density, and which can therefore be precomputed and tabulated. Skartlien (2000) and Hayek et al (2010) showed the importance of photon scattering in simulations of the higher solar atmosphere; we therefore include a coherent scattering contribution in the gas emission, which requires an iterative solution of the radiative transfer equation to obtain a consistent radiation field. The vast number of spectral lines encountered in a stellar atmosphere requires, in principle, the solution of a large number of radiative transfer problems.…”
Section: Full Radiative Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore assume a static medium and LTE for the gas opacity, which thus depends only on the local gas temperature and the gas density, and which can therefore be precomputed and tabulated. Skartlien (2000) and Hayek et al (2010) showed the importance of photon scattering in simulations of the higher solar atmosphere; we therefore include a coherent scattering contribution in the gas emission, which requires an iterative solution of the radiative transfer equation to obtain a consistent radiation field. The vast number of spectral lines encountered in a stellar atmosphere requires, in principle, the solution of a large number of radiative transfer problems.…”
Section: Full Radiative Transfermentioning
confidence: 99%
“…If the hydrodynamical timesteps are sufficiently short that changes in the radiative energy flux are small, full radiative transfer only needs to be computed in a fraction of the hydrodynamical timesteps. A detailed description of the numerical methods and the parallelization techniques used for the full radiative transfer module in Bifrost can be found in Hayek et al (2010).…”
Section: Full Radiative Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Opacities were based on OSMARCS model opacities (these models are used in Appendix A), which were binned into 14 opacity groups (Nordlund 1982;Ludwig et al 1994). The effect of scattering was treated according to the Hayek et al (2010) approximation as explored by Collet et al (2011); scattering opacities in the deeper layers of the model are treated as true absorption and ignored in the outer regions of the model atmosphere (see Ludwig & Steffen 2013, for a full description). As all models used are metal poor, the alpha elements were enhanced so that [α/Fe] = +0.4.…”
Section: Co 5 Bold Model Computationsmentioning
confidence: 99%
“…Recently Hayek et al (2010) have introduced a proper treatment of scattering in their magneto-hydrodynamical simulation code, BIFROST. For the Sun and solar-type stars they do not find a significant impact of continuum scattering on the temperature structure.…”
Section: Hydrodynamical Models and Spectrum Synthesismentioning
confidence: 99%